Ergonomic analysis work: Emphasis on the postural condition of telemarketing operators (Research, Society and Development, 2022)
The conservation of proper posture is important for humans, because the correct posture transmits comfort and well-being. The poor posture generates some diseases that contribute to increases in the rates of disabilities and removal of employees. This article analyzes the postural condition exercised by the attendants of a telemarketing, and as a specific objective, to identify the work performed by the attendants, and the ergonomic working conditions of the telemarketing work units, using ergonomic analysis tools of the work, with the analysis of the postural condition performed by the attendants of a telemarketing, are in accordance with the regulatory standard NR17. The procedure used for the structuring of this study consisted of the institution's documental analysis for data collection, through the employee book and the environmental risk prevention program and the occupational health control program and the identification of risks in the sitting posture exercised by the employees. Thus, the tools were applied to observe ergonomic criteria, through the Ergolandia 8.0 software it was possible to measure the scores of the methods performed in postural analysis. Tools such as Ovako work posture analysis system, rapid upper limb evaluation, rapid evaluation of the whole body and NR17 were used. As a result, suggestions were made to improve the work environment and the posture of employees. The main suggestions were to perform postural and ergonomic training, take breaks at work, adjust the chairs and equipment in the work environment, practice of work gymnastics, which is implemented occupational risk prevention program, providing more comfort, well-being, health and safety for workers.